Endoplasmic Reticulum Stress of Gut Enterocyte and Intestinal Diseases - Gao, Han; He, Chengwei; Hua, Rongxuan; Guo, Yuexin; Wang, Boya; Liang, Chen; Gao, Lei; Shang, Hongwei; Xu, Jing-Dong (Frontiers in Molecular Biosciences, 2022)
The endoplasmic reticulum, a vast reticular membranous network from the nuclear envelope to the plasma membrane responsible for the synthesis, maturation, and trafficking of a wide range of proteins, is considerably sensitive to changes in its luminal homeostasis. The loss of ER luminal homeostasis leads to abnormalities referred to as endoplasmic reticulum stress (ER stress). Due to this, the cell activates an adaptive response known as the unfolded protein response (UPR), a mechanism to stabilize ER homeostasis under severe environmental conditions. ER stress has recently been postulated as a disease research breakthrough due to its significant role in multiple vital cellular functions. This has caused numerous reports that ER stress-induced cell dysfunction has been implicated as an essential contributor to many disease occurrence and development, resulting in them targeting the relief of ER stress. This review aims to outline the multiple molecular mechanisms of ER stress that can elucidate ER as an expansive, membrane-enclosed organelle playing a crucial role in numerous cellular functions with evident changes of several cells encountering ER stress. Alongside, we mainly focused on the therapeutic potential of ER stress inhibition in gastrointestinal diseases such as Inflammatory bowel disease (IBD) and colorectal cancer. To conclude, we reviewed advanced researches and highlighted future treatment strategies of ER stress-associated conditions.